Essential Oil Constituents of Two African Olibanums Available in Isfahan Commercial Market: Essential oils of olibanums - Afsharypuor, Suleiman; Rahmany, Marzieh (Iranian Journal of Pharmaceutical Sciences, 2005)
The composition of the essential oils of two African (“white” and “yellow”) olibanums available in the commercial market of Isfahan (Iran) was analyzed by gas chromatography (GC) and GC-mass spectroscopy methods. The main constituents of the “White” olibanum oil were alpha-pinene (34.8%), limonene (15.9%), alphathujene (9.0%), para-cymene (7.0%), myrcene (6.2%) and sabinene (6.0%). Major components of the “yellow” olibanum oil were alpha-pinene (48.0%), limonene (21.7%), myrcene (4.9%), beta-caryophyllene (4.9%) and para-cymene (3.5%).